2020
DOI: 10.1159/000509290
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 (SARS-CoV-2) Infection in Pregnancy: A Systematic Review

Abstract: Introduction: To review published studies related to the association of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections with pregnancy, foetal, and neonatal outcomes during coronavirus disease 2019 (COVID-19) pandemic in a systematic manner. Methods: A comprehensive electronic search was done through PubMed, Scopus, Medline, Cochrane database, and Google Scholar from December 01, 2019, to May 22, 2020, along with the reference list of all included studies. All cohort studies that report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
2
20

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(173 citation statements)
references
References 34 publications
(81 reference statements)
4
131
2
20
Order By: Relevance
“…After the application of the eligibility criteria, 39 studies were finally included [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ], one (2.6%) of which was described as “rapid” [ 42 ] and two (5.1%) as “scoping” systematic reviews [ 30 , 50 ]. Thirteen (33%) of them also undertook a meta-analysis [ 14 , 16 , 18 , 19 , 24 , 25 , 27 , 36 , 38 , 40 , 48 ,…”
Section: Resultsmentioning
confidence: 99%
“…After the application of the eligibility criteria, 39 studies were finally included [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ], one (2.6%) of which was described as “rapid” [ 42 ] and two (5.1%) as “scoping” systematic reviews [ 30 , 50 ]. Thirteen (33%) of them also undertook a meta-analysis [ 14 , 16 , 18 , 19 , 24 , 25 , 27 , 36 , 38 , 40 , 48 ,…”
Section: Resultsmentioning
confidence: 99%
“…Despite initial concern that pregnant women and the newborn may be high-risk groups compared with the general population based on outbreaks of other coronavirus diseases in the past, it has become increasingly clear that this is not the case with the SARS-CoV2 pandemic. [6][7][8][9][10][11] The risk of vertical transmission of the virus from mother to infant before or during delivery has been shown to be low. [7][8][9][10][11] This has been confirmed based on virus testing and clinical features in our cohort, with the estimated risk being only 2.7% (2/73).…”
Section: Discussionmentioning
confidence: 99%
“…6 The literature published so far on COVID-19, however, suggests that hospitalised pregnant women do not seem to be at a higher risk of adverse outcomes compared with hospitalised non-pregnant individuals. [6][7][8] The risk of vertical transmission to infants born to mothers with COVID-19 seems low. [7][8][9][10][11] In the few infants who tested positive following birth, it was not certain whether the transmission was vertical or postnatal and further, the majority of these infants had only mild-tomoderate disease.…”
Section: Introductionmentioning
confidence: 99%
“…Since December 2019 when the infection was first identified, more than 41,000 MEDLINEindexed papers have been published on COVID-19. Up to 31st July 2020, at least 29 systematic reviews on COVID-19 and pregnancy with varying conclusions have been published (Abdollahpour and Khadivzadeh 2020;Akhtar et al 2020;Ashraf et al 2020;Capobianco et al 2020;Della Gatta et al 2020;Deniz and Tezer 2020;Di Mascio et al 2020;Dubey et al 2020;Elshafeey et al 2020;Hessami et al 2020;Juan et al 2020;Kasraeian et al 2020;Kotlyar et al 2020;Lopes de Sousa et al 2020;Matar et al 2020;Melo and Araújo 2020;Muhidin et al 2020;Segars et al 2020;Silva et al 2020;Smith et al 2020;Thomas et al 2020a, b;Trippella et al 2020;Trocado et al 2020;Turan et al 2020;Walker et al 2020;Yang et al 2020;Yoon et al 2020;Zaigham and Andersson 2020). Factors which are likely to cause bias and thus, inaccuracy in subsequent analysis in systematic reviews were then identified and compiled.…”
Section: Methodsmentioning
confidence: 99%